PENGINDERAAN JAUH UNTUK ZONASI KERENTANAN RAWAN PANGAN BERDASARKAN KONDISI BIOFISIK LAHAN DI KABUPATEN PURWOREJO - PRIMA WIDAYANI (Jurnal Agroteknologi, 2014)
Food is a basic need that the demand is increasing in line with the population growth. A new approach of agricultural development is needed in order to fulfill the food need in the present and the future. The approach is to determine the food security in a region by using the Food Security Atlas. The previous atlas is still in the national scale, so it needs additional researches in the local scale. This study aims to create a map of food vulnerability in the Purworejo district as an input to determine the food security. The parameters used to create the vulnerability map are the percentage of vegetated land area, rainfall anomalies, the percentage of crop failure area due to flood or pests, and land degradation due to erosion. Remote sensing data are used to create the percentage of vegetated land area map, land use map, land unit map, flood and erosion map. All parameters are given values to classify the food vulnerability. The results show that the vulnerable regions are not only in the transition area between hills and plain area, which are in Bruno, Pituruh, Kemiri, Kaligesing, and Loano sub-district, but also in the southern coastal region, which are in Ngombol and Grabag sub-district. Calculation show that the area of food secured regions in Purworejo are 63,11 km2, the secured enough regions are 804.96 km2, while the vulnerable regions are 218,24 km2 .